Comics and Migration Representation and Other Practices - Kauranen, Ralf; Löytty, Olli; Nikkilä, Aura; Vuorinne, Anna (Global Perspectives in Comics Studies, 2023)
comics, migration, comics studies, representation, applied uses of comics